PENGARUH IMPLEMENTASI KEBIJAKAN APLIKASI HIPPOCAMPUS (MEDIA PEMBELAJARAN) SARANA PRASARANA DAN KOMPETENSI GURU TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMAS PLUS PERMATA INSANI ISLAMIC SCHOOL - Sari, Kokom Komala; Kamil, Mustafa; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the effect of Hippocampus Application Policy Implementation (Learning Media), Facilities and Infrastructure, and Teacher Competence on Learning Effectiveness at SMAS Plus Permata Insani Islamic School. The research employed a quantitative approach with a survey method. The population consisted of 34 teachers, and data were collected through a Likert-scale questionnaire. Validity and reliability tests indicated that all instrument items were valid (corrected item-total correlation >= 30) and reliable (Cronbach’s Alpha 0.915). Data analysis was conducted using multiple linear regression. The results revealed that simultaneously, the three independent variables had a significant effect on learning effectiveness (R²=0.792; F=36.812; Sig.=0.000). Partially, teacher competence had the most dominant influence (Beta = 0.471; Sig. 0.004), followed by Hippocampus Application Policy Implementation (Beta = 0.293; Sig. 0.051), while Facilities and Infrastructure showed a significant effect at the 10% level (Beta = 0.213; Sig. 0.086). These findings emphasise that improving digital application-based learning effectiveness requires adequate teacher competence, consistent policy implementation, and sufficient facilities and infrastructure support. Keywords: Hippocampus Application, Facilities and Infrastructure, Teacher Competence, Learning Effectiveness, Multiple Linear Regression